The Influence of Manpower Training Development on the Operational Performance of Vehicle Units in Fleet User Businesses - Zulfa Laila Nur Azkiya'; Zainal Arifin (STKIP Singkawang, 2025)
This study aims to analyze (1) the training development patterns implemented in manpower training for fleet users and (2) the influence of manpower training development on the operational performance of fleet user vehicle units. This research employs a qualitative descriptive method, focusing on the impact of manpower training development on the operational performance of vehicles within the fleet user business. Data collection techniques include document analysis, interviews, and observations. Credibility, transferability, dependability, and confirmability are applied to ensure the validity of the data. The data analysis technique uses the interactive model of Miles, Huberman, and Saldaña, which consists of three stages, namely: (1) data condensation, (2) data presentation, and (3) conclusion drawing/verification. The findings reveal that (1) the training pattern adopted in both training programs within the fleet user business follows a tiered structure, and (2) manpower training development significantly influences the fleet user business in maintaining an operational target of 90%. This is attributed to the improvement in mechanical expertise, which enables mechanics to gain a better understanding of work procedures in accordance with standard operating procedures (SOPs) and to identify necessary maintenance and repair measures. The enhancement of mechanical skills positively impacts vehicle unit performance, as evidenced by the Physical Availability (PA) of vehicles reaching 99% in November 2024, exceeding the set target of 90%. Additionally, the study highlights a substantial increase in fleet user business revenue, with a growth of 33% in 2023 and a further increase of 50% in 2024.